2014
DOI: 10.1186/cc13977
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of different diagnostic criteria of acute kidney injury in critically ill patients

Abstract: IntroductionRecently, the Kidney Disease: Improving Global Outcomes (KDIGO) proposed a new definition and classification of acute kidney injury (AKI) on the basis of the RIFLE (Risk, Injury, Failure, Loss of kidney function, and End-stage renal failure) and AKIN (Acute Kidney Injury Network) criteria, but comparisons of the three criteria in critically ill patients are rare.MethodsWe prospectively analyzed a clinical database of 3,107 adult patients who were consecutively admitted to one of 30 intensive care u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
172
4
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(203 citation statements)
references
References 31 publications
(37 reference statements)
9
172
4
6
Order By: Relevance
“…17 Similar findings were also reported in a study with 3100 critically ill patients. 5 KDIGO identified more patients with AKI than RIFLE (51% vs. 46.9%; p ¼ 0.001) or AKIN (51% vs. 38.4%; p < 0.001). Therefore, based on currently available evidence, KDIGO is at least as good as, and in some situations even better than the AKIN and RIFLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Similar findings were also reported in a study with 3100 critically ill patients. 5 KDIGO identified more patients with AKI than RIFLE (51% vs. 46.9%; p ¼ 0.001) or AKIN (51% vs. 38.4%; p < 0.001). Therefore, based on currently available evidence, KDIGO is at least as good as, and in some situations even better than the AKIN and RIFLE.…”
Section: Discussionmentioning
confidence: 99%
“…4 Study by Luo et al 5 showed that KDIGO identified more patients with AKI than RIFLE or AKIN classification system. The etiology of AKI is often multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…Seven observational studies251, 252, 253, 254, 255, 256, 257 examining patient mortality rate as a clinical outcome were extracted during an assessment comparing the KDIGO guidelines and the AKIN and RIFLE criteria, and as a result of comparing AKI diagnoses based on the KDIGO guidelines with diagnoses based on the RIFLE or AKIN criteria, diagnoses based on the AKIN criteria were found to have higher accuracy or were reflective of similar in‐hospital mortality rates. Although only the study by Peng et al 257.…”
Section: Cq12: Acute Kidney Injury/blood Apheresismentioning
confidence: 99%
“…31 Based on the maximum value of available postoperative creatinine, patients were categorized in mutually exclusive categories of creatinine change and corresponding stages of AKI according to the KDIGO definition, 27 including no follow-up (no F/U), no measured increase (ΔCr ≤ 0%), slight increase (ΔCr 1 to 24%), minor increase (ΔCr 25 to 49%), KDIGO stage 1 (ΔCr 50 to 99%, corresponding to RIFLE R or AKIN 1), KDIGO stage 2 (ΔCr 100 to 199%, RIFLE I or AKIN 2), and KDIGO stage 3 (ΔCr ≥ 200%, RIFLE F or AKIN 3). 27,29,30 According to KDIGO guidelines, patients were categorized to the highest category possible.…”
Section: Definition Of Aki and Aki Severitymentioning
confidence: 99%